THE RELATIONSHIP BETWEEN HEALTH LITERACY AND HEALTH BEHAVIOR 3E 2S OF MONKS AMONG KHUN HAN DISTRICT, SISAKET PROVINCE - ปัญญา นิสา; ห้วยทราย วุฒิฌาน; อุ่นแก้ว ธิราภรณ์; มนตรีวงษ์ วชิราภรณ์ (Primary Health Care Journal (Northeastern Edition), 2024)
This cross-sectional research aims to investigate the relationship between health literacy and health behaviors 3E 2S among monks in Khun Han District, Si Sa Ket Province. The sample group consisted of 148 monks selected through simple random sampling from April to June 2023. Data were collected using questionnaires and analyzed using descriptive statistics, including frequency distribution, percentages, means, standard deviations, maximum, and minimum values. Additionally, the relationship between health literacy and health behaviors was analyzed using the Chi-square test. The research findings revealed that the majority of the sample group were temple monks (75.0%), with a mean age of 48.8 years (SD = 17.27) and an average monastic experience of 7.8 years (SD = 9.21). Most had completed primary education (24.3%) without studying Dhamma or Pali (41.2%) and had no chronic illnesses (81.1%). Regarding health knowledge, the majority had adequate levels (61.5%), while most health behaviors (3E 2S) were at an unsatisfactory level (83.1%). The relationship between health literacy and health behaviors (3E 2S) was statistically significant at the .05 level. Therefore, there should be activities implemented to enhance health knowledge among monks to facilitate appropriate health behavior modifications in the future.